Implementasi Pembelajaran Berbasis Masalah yang Didukung oleh Buku Pop-Up untuk Meningkatkan Kemampuan Berpikir Kritis dan Hasil Belajar Siswa - Silvia Anggraini; Erianjoni Erianjoni; Azmi Azmi; Darmansyah Darmansyah (Universitas Hamzanwadi, 2025)
Critical thinking skills of each student significantly influence their cognitive development and adaptability. However, many students still exhibit low levels of critical thinking, which requires immediate attention. This study aims to improve students' critical thinking skills through the implementation of a Problem-Based Learning (PBL) model supported by Pop-Up Book media in Grade X Phase Eat SMAN 1 Padang. This research is classroom action research (CAR). The instructional interventions were delivered by the teacher or conducted by students under the teacher's guidance. The teacher reported on students' learning processes, observed student behavior and engagement, analyzed the outcomes, recorded findings, facilitated peer discussions, and guided class presentations. The classroom action research followed a cyclical model consisting of four main stages: action planning (pre-intervention), action implementation, observation, and reflection. This study was conducted over two cycles, with each cycle consisting of two sessions. Each cycle included the same four phases: planning, implementation, observation, and reflection. In the first cycle, despite some challenges, the implemented learning model demonstrated visible progress. The class average score increased from 47.19 in the pretest to 77.09 after the first cycle, and further improved to 80 in the second cycle. These results indicate that the Problem-Based Learning model supported by Pop-Up Book media had a positive impact on students' critical thinking skills and learning outcomes. Overall, the study concludes that the application of Problem-Based Learning supported by Pop-Up Book media effectively enhanced students' academic achievement at SMAN 1 Padang.